(untitled) (The Strategic Review for Southern Africa, 2023)
Zimbabwe's political landscape has undergone significant changes since the 2017 coup, with the post-coup period being christened the ‘New Dispensation’. The advent of the ‘New Dispensation’, characterised with promises of a new and revolving democracy, coincided with the coming of voting age of ‘Ama 2000’. The paper investigated the electoral participation of ‘Ama 2000’ in Zimbabwe’s 2023 elections. A theoretical framework that looked at factors that influence youth political participation was developed and used in explaining the electoral participation or their lack thereof. 115 focus group respondents between the ages of 18 to 23 were selected in Zimbabwe’s cities of Harare and Bulawayo, wherein conversations on the motivations and barriers on youth political engagement were facilitated. Whilst ‘Ama 2000’ demonstrated political knowledge and interest, they are generally apathetic, with a few participating in voting whilst most did not associate with the other forms of electoral participation. Disillusionment with both politicians and political parties, politically motivated violence, and life cycle factors were the major reasons for their lack of interest in the country’s 2023 elections. Arguably, there is no democratic and plural ‘New Dispensation’ after all, as these same factors have deterred older youth from participating in elections under the authoritarian Mugabe regime. However, the limited participation of ‘Ama 2000’ in voting demonstrates commitment to democratic principles and a desire to shape the country's future. To address the youth apathy gap, political parties must actively engage with them, reform and promote inclusivity. At state level, structural reforms of an electoral nature are necessary to protect the security of the voter. Civil society has a role to play in strengthening civic education programs that instill a sense of civic duty and active participation in democracy. By involving youth in the democratic process, Zimbabwe can build a foundation for inclusive political participation.